New Cancer Treatment Methods - Makhmatkulova G. M.; Asatulaev Akmal Farxatovich (Scholars Digest Publishing, 2023)
The problem of oncology is one of the most pressing in the world. Almost half of the world's population has cancer. This disease affects not only adults but also children. In order to draw public attention to this global problem, the International Union Against Cancer was created, which conveys information about how dangerous and widespread cancer is. In recent years, medicine has made great strides. However, cancer is still not fully understood. Issues of diagnosis, treatment and prevention remain open. Oncological diseases are a vast and heterogeneous class of diseases, they are systemic and affect, in one way or another, all organs and systems of a person. Patients often perceive an oncological diagnosis as a death sentence, but not all, even malignant, tumors are fatal. No possible disease causes as many fears and myths as malignancy or cancer.
Keywords: Cancer, prevention, malignant neoplasm.